Leishmaniasis in the contemporary clinical context and its therapeutics interventions: A review - Chammas, Sergio Mestieri; Reys, Mercedes Hernandes; Rabelo, Daniel da Conceição; Yoshikawa, Guilherme Hiromi; Machado, Álvaro Jorge Laiso; Maria, Durvanei Augusto (Seven Editora, 2024)
Leishmaniasis is a tropical disease categorized as neglected due to its impact on populations with limited access to resources. It is caused by various species of the parasite Leishmania, belonging to the Trypanosomatidae family within the order Kinetoplastida, and transmitted by sandflies (Phlebotomine sandflies) during the female’s blood meal. Several mammal species, which often coexist closely with humans, serve as biological reservoirs. Leishmaniasis manifests in different forms, including cutaneous (CL), diffuse (DCL), mucocutaneous (MCL), visceral (VL), post-kala-azar dermal (PKDL), and mucosal (ML). In this context, our objective is to provide updated information to facilitate access to data for various specialists dealing with this parasitic disease. Simultaneously, we aim to contribute to public education, particularly among populations facing precarious living conditions and challenges in accessing healthcare services in endemic areas. A total of 135 articles on Leishmania were reviewed, sourced from 95 journals. This endeavor serves as a means to identify potential risks and formulate strategies for preventing and mitigating the consequences of leishmaniasis. DOI:https://doi.org/10.56238/sevened2024.009-027